2011
DOI: 10.1128/jb.06241-11
|View full text |Cite
|
Sign up to set email alerts
|

Ribulokinase and Transcriptional Regulation of Arabinose Metabolism in Clostridium acetobutylicum

Abstract: The transcription factor AraR controls utilization of L-arabinose in Bacillus subtilis. In this study, we combined a comparative genomic reconstruction of AraR regulons in nine Clostridium species with detailed experimental characterization of AraRmediated regulation in Clostridium acetobutylicum. Based on the reconstructed AraR regulons, a novel ribulokinase, AraK, present in all analyzed Clostridium species was identified, which was a nonorthologous replacement of previously characterized ribulokinases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 37 publications
1
52
1
Order By: Relevance
“…A DNA microarray analysis has shown that this gene was strongly induced by arabinose (33). We have found that expression of this xfp gene was regulated by the transcriptional factor AraR, which controls arabinose utilization in C. acetobutylicum (48). Moreover, we have detected the xylulose-5-P phosphoketolase activity in C. acetobutylicum grown on arabinose by using the in vitro enzyme assay (data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…A DNA microarray analysis has shown that this gene was strongly induced by arabinose (33). We have found that expression of this xfp gene was regulated by the transcriptional factor AraR, which controls arabinose utilization in C. acetobutylicum (48). Moreover, we have detected the xylulose-5-P phosphoketolase activity in C. acetobutylicum grown on arabinose by using the in vitro enzyme assay (data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…Abbreviations are as follows: XynT, sugar/Na + (H + ) simporter; AraE1/AraE2/XylT, sugar-proton symporter; XylA, xylose isomerase [43]; XynB, Beta-xylosidase; XylB, xylulose kinase; Tkt1/Tkt2, transketolase; Tal, transaldolase; AraA1/AraA2, L-arabinose isomerase; AraK, ribulokinase [44]; AraD, L-Ribulose-5-phosphate 4-epimerase; ScrA, beta-glucosides specific PTS IIBCA component; ScrB, sucrase-6-phosphate hydrolase; ScrK, fructokinase; MltF, mannitol-specific PTS IIA component; MtlA, mannitol-specific PTS IIBC component; MtlD, mannitol-1-phosphate 5-dehydrogenase; FruB, 1-phosphofructokinase; Pmi, phosphomannose isomerase; GlvA, maltose-6-phosphate glucosidase; GlgC, glucose-1-phosphate adenylyltransferase; GlgA, starch synthase; LacG, 6-phospho-beta-galactosidase; LacA, galactose-6-phosphate isomerase subunit A; LacB, galactose-6-phosphate isomerase subunit B; LacC, tagatose-6-phosphate kinase; GatY, tagatose-bisphosphate aldolase; GalK, galactokinase; GalT, galactose-1-phosphate uridylyltransferase; GalE, UDP-galactose 4-epimerase; GlpK, glycerol kinase; GlpA, glycerol-3-phosphate dehydrogenase; GanA, arabinogalactan endo-1,4-beta-galactosidase; GlpF, glycerol uptake facilitator protein; GlcK, glucokinase; GlvG, 6-phospho-alpha-glucosidase; GlgC, glucose 1-phosphate adenylyltransferase; GlgA, glycogen synthase; AraT , arabinosides-proton symporter [44]; Arb43, Alpha-L-arabinofuranosidase II precursor [44]; Ptk, phosphoketolase; Rpi, ribose 5-phosphate isomerase; Rpe, aldose-1-epimerase; Epi, arabinose mutarotase; GAP, glyceraldehyde 3-phosphate; F1P, fructose 1-phosphate; F6P, fructose 6-phosphate; FBP, fructose 1,6-biphosphate; G6P, glucose 6-phosphate; G1P, glucose 1-phosphate; C6P, cellobiose 6-phosphate; Xylu5P, xylulose 5-phosphate; DHA, dihydroxyacetone.…”
Section: Resultsmentioning
confidence: 99%
“…Only an alternative xylose isomerase gene, xylA-II (CAC2610), was identified in C. acetobutylicum (Gu et al, 2010). However, both xylA-II and xylB may be essential for xylose metabolism in C. acetobutylicum because inactivation of either gene resulted in the loss of xylose consumption (Gu et al, 2010;Xiao et al, 2011;Zhang et al, 2012). xylA-II (CAC2610) is required for converting xylose into xylulose during the first step of xylose metabolism, and CAC2610 exhibited 14.97 times stronger expression in +SS than in ÀSS.…”
Section: Expression Of Sugar Metabolism Genesmentioning
confidence: 99%